Electronic gaming and psychosocial adjustment - Przybylski, A (American Academy of Pediatrics, 2014)
BACKGROUND AND OBJECTIVES: The rise of electronic games has driven both concerns and hopes regarding their potential to influence young people. Existing research identifies a series of isolated positive and negative effects, yet no research to date has examined the balance of these potential effects in a representative sample of children and adolescents. The objective of this study was to explore how time spent playing electronic games accounts for significant variation in positive and negative psychosocial adjustment using a representative cohort of children aged 10 to 15 years. METHODS: A large sample of children and adolescents aged 10 to 15 years completed assessments of psychosocial adjustment and reported typical daily hours spent playing electronic games. Relations between different levels of engagement and indicators of positive and negative psychosocial adjustment were examined, controlling for participant age and gender and weighted for population representativeness. RESULTS: Low levels (<1 hour daily) as well as high levels (>3 hours daily) of game engagement was linked to key indicators of psychosocial adjustment. Low engagement was associated with higher life satisfaction and prosocial behavior and lower externalizing and internalizing problems, whereas the opposite was found for high levels of play. No effects were observed for moderate play levels when compared with non-players. CONCLUSIONS: The links between different levels of electronic game engagement and psychosocial adjustment were small (<1.6% of variance) yet statistically significant. Games consistently but not robustly associated with children's adjustment in both positive and negative ways, findings that inform policy-making as well as future avenues for research in the area.